2017
DOI: 10.1002/clc.22836
|View full text |Cite
|
Sign up to set email alerts
|

Association between ideal cardiovascular health metrics and risk of cardiovascular events or mortality: A meta‐analysis of prospective studies

Abstract: Background Observational studies evaluating the relationship between ideal cardiovascular health (CVH) metrics and risk of cardiovascular (CV) events and mortality yielded inconsistent results. Hypothesis Improvement in CVH metrics can result in substantial reductions in the risk of cardiovascular disease (CVD), stroke, and mortality. Methods We examined associations between ideal CVH metrics and CV events and mortality by conducting a meta‐analysis of data from prospective cohort studies identified by searchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
98
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(111 citation statements)
references
References 36 publications
7
98
1
5
Order By: Relevance
“…Prior studies have evaluated the association of ideal CVH and clinical endpoints. 16,18,31,[33][34][35] In conclusion, in a community-based study of black and white participants with low prevalence of ideal CVH, even achieving 3 or more ideal CVH factors was associated with lower burden of subclinical atherosclerosis, indicating the utility of this construct for disease prevention.…”
Section: As Shown Inmentioning
confidence: 88%
See 1 more Smart Citation
“…Prior studies have evaluated the association of ideal CVH and clinical endpoints. 16,18,31,[33][34][35] In conclusion, in a community-based study of black and white participants with low prevalence of ideal CVH, even achieving 3 or more ideal CVH factors was associated with lower burden of subclinical atherosclerosis, indicating the utility of this construct for disease prevention.…”
Section: As Shown Inmentioning
confidence: 88%
“…Finally, our focus was primarily on studying the relationship between ideal CVH and subclinical CVD including microvascular endothelial function, and so we have not looked at clinical CVD outcomes in these analyses. Prior studies have evaluated the association of ideal CVH and clinical endpoints …”
Section: Discussionmentioning
confidence: 99%
“…We observed that the increased ideal CVH metrics number was significantly associated with reduced CVD prevalence in most sex and age subgroups and the dose-response fashion was also noticed in a few recent meta-analyses. 14,141 The number of ideal metrics has more significant influences on CVD prevalence in men compared with women in our study. Two studies indicated the association strengths between the number of ideal CVH metrics and HF incidence/asymptomatic ICAS prevalence were similar in both sexes 91,145 whereas several studies found that males are more likely to influenced by the CVH metrics for CVD events 29,150 and stroke.…”
Section: Discussionmentioning
confidence: 69%
“…Given the advantages of Life's Simple 7, a number of studies have used Life's Simple 7 to measure the CVH status in the general population 11,12 and explored its association with CVD/IHD risk. 13,14 Most studies implied the low prevalence of the ideal CVH status in the general population and indicated the significant separate and combined effects of the CVH status on CVD/IHD risk.…”
Section: List Of Figuresmentioning
confidence: 99%
See 1 more Smart Citation